A waterproof composite material and preparation method thereof

By adopting a three-layer waterproof composite material, combining ultralight polyethylene materials, ceramic granules and porous ceramics, cement mortar and high-water absorption resin, and polyester fiber materials, the existing waterproof materials have limited waterproofing capabilities in coal mine underground environments, and the material's performance improvement is achieved, which is suitable for long-term use in complex environments.

CN119734489APending Publication Date: 2025-04-01SHAANXI TONGREN APPLIED MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967973.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing waterproof materials have limited waterproofing capabilities in underground coal mine environments, and their waterproofing performance decreases after long-term use, which cannot meet the demand for rapid treatment of large amounts of accumulated water.

Method used

A waterproof composite material with a three-layer structure includes a bottom layer, a water absorbent layer and a protective layer. The bottom layer is made of ultralight polyethylene material, the water-absorbing layer consists of ceramic particles and porous ceramics, mixed with cement mortar and high-water-absorbing resin, the protective layer is made of polyester fiber material, and anti-slip raised particles and luminescent particles are provided on the surface.

Benefits of technology

It has achieved significant improvements in water absorption, mechanical strength, chemical corrosion resistance, wear resistance, slip resistance, durability and environmental protection in waterproof composite materials. It has extremely high water absorption capacity and rapid drainage characteristics, which is suitable for long-term and stable work in complex environments, reduces maintenance costs and simplifies the construction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734489A_ABST
    Figure CN119734489A_ABST
Patent Text Reader

Abstract

The present application discloses a waterproof composite material and a preparation method thereof, wherein the waterproof composite material comprises: a base layer, a water absorbing layer and a protective layer which are sequentially stacked and bonded, wherein the water absorbing layer is used to absorb and store external moisture; the base layer is used to block the moisture stored in the water absorbing layer; and the protective layer is used to provide physical protection for the water absorbing layer and the base layer. The present application can improve the waterproof ability of existing waterproof materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of waterproof materials and preparation thereof, and specifically relates to a waterproof composite material and a preparation method thereof. Background Art

[0002] During the underground mining process, water often accumulates underground, which not only threatens the safe operation of the mine, but also seriously affects the construction environment of the workers, increasing the risk and difficulty of the operation. Although traditional waterproofing measures can partially slow down the seepage, they are often difficult to meet the complex and changing needs of the underground environment. Therefore, it is of great practical significance to develop an efficient and durable water-absorbing composite material that can be used on the ground underground in coal mines.

[0003] In the prior art, many composite materials are used for waterproofing, but the waterproofing ability of most materials is limited, or the waterproofing performance deteriorates after long-term use, and cannot meet the needs of quickly handling large amounts of accumulated water. Summary of the invention

[0004] The main purpose of the present application is to provide a waterproof composite material and a preparation method thereof, aiming to solve the problem of limited waterproof ability of existing waterproof materials.

[0005] To achieve the above objectives, this application provides the following technical solutions:

[0006] A waterproof composite material, comprising: a base layer, a water absorbing layer and a protective layer which are stacked and attached in sequence, wherein the water absorbing layer is used to absorb and store external moisture; the base layer is used to block the moisture stored in the water absorbing layer; and the protective layer is used to provide physical protection for the water absorbing layer and the base layer.

[0007] Optionally, the water-absorbing layer includes ceramsite and porous ceramics, and the pores between the ceramsite and the porous ceramics are mixed and filled with cement mortar and highly absorbent resin.

[0008] Optionally, the ceramsite and the porous ceramic are arranged in a set shape.

[0009] Optionally, the components of the cement mortar and the mass percentage of each component are: 1% to 10% mineral powder, 1% to 5% nano-silica fume, 10% to 15% cement, 10% to 30% fast-hardening sulphoaluminate cement, 10% to 25% 40 to 70 mesh river sand, and 10% to 25% 70 to 40 mesh river sand.

[0010] Optionally, the components of the super absorbent resin and the mass percentage of each component are: rice husk ash 7% to 20%, acrylic acid 16% to 35%, sodium hydroxide solution 7% to 30%, acrylamide 4% to 22%, benzoyl peroxide 0.3% to 0.6%, borax 0.01% to 1%, and flame retardant 0.1% to 0.4%.

[0011] Optionally, the protective layer is made of polyester fiber material.

[0012] Optionally, anti-skid protrusion particles are provided on the protective layer, and the anti-skid protrusion particles are arranged in order at fixed intervals on the protective layer.

[0013] Optionally, luminous particles are further provided on the protective layer, and the luminous particles are evenly distributed between the anti-slip protrusion particles.

[0014] Optionally, the bottom layer is made of ultra-light polyethylene material.

[0015] In addition, the present application also provides a method for preparing a waterproof composite material, which includes: pre-treating a base layer, a water-absorbing layer and a protective layer; applying an adhesive to the surface of the pre-treated base layer, heating to partially cure the adhesive, placing the pre-treated water-absorbing layer on the partially cured adhesive, and heating again to completely cure the adhesive so that the pre-treated base layer and the water-absorbing layer are bonded; applying an adhesive to the surface of the water-absorbing layer after bonding with the base layer, heating to partially cure the adhesive, laying the pre-treated protective layer on the partially cured adhesive, and heating again to completely cure the adhesive so that the pre-treated protective layer and the water-absorbing layer are bonded, thereby forming a waterproof composite material.

[0016] The present application can achieve the following beneficial effects: By using ultra-light polyethylene material as the bottom layer, combined with an optimized water-absorbing layer and a multifunctional protective layer, the present application achieves a significant improvement in water absorption rate, mechanical strength, chemical corrosion resistance, wear resistance, anti-slip performance, durability and environmental protection of the waterproof composite material. The composite material not only has extremely high water absorption capacity and rapid drainage characteristics, but also can work stably for a long time in complex environments, reducing maintenance costs and simplifying the construction process. Its excellent comprehensive performance and adaptability are particularly suitable for harsh working conditions such as underground coal mines, significantly improving safety and economic benefits, and reflecting obvious superiority and innovation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic structural diagram of a waterproof composite material provided by an embodiment of the present application;

[0018] Figure 2 Another embodiment of the present application provides ceramsite and porous ceramic arranged in a tic-tac-toe shape;

[0019] Figure 3 Another embodiment of the present application provides ceramsite and porous ceramic arranged in a cross shape;

[0020] Figure 4 Another embodiment of the present application provides a porous ceramic of ceramsite arranged in a wave shape;

[0021] Figure 5 is a schematic diagram of the distribution of luminous particles and anti-slip protrusion particles provided in another embodiment of the present application;

[0022] Figure 6 It is a schematic flow chart of a method for preparing a waterproof composite material provided in another embodiment of the present application.

[0023] The following are the descriptions of the reference numerals:

[0024] 100, bottom layer; 200, water absorption layer; 300, protective layer; 210, porous ceramics; 220, expanded clay; 310, anti-slip raised particles; 320, luminous particles. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0027] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0028] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0029] Figure 1 Schematic diagram of a waterproof composite material according to an embodiment of the present application. Figure 1 As shown, the waterproof composite material includes: a base layer 100, a water-absorbing layer 200 and a protective layer 300 which are stacked and attached in sequence, wherein the water-absorbing layer 200 is used to absorb and store external moisture; the base layer 100 is used to block the moisture stored in the water-absorbing layer 200; and the protective layer 300 is used to provide physical protection for the water-absorbing layer 200 and the base layer 100.

[0030] The present application provides a waterproof composite material with a three-layer structure. The waterproof composite material with a three-layer structure has excellent waterproof performance, enhanced mechanical strength and durability, and the ability to adapt to complex environments through the bottom layer preventing water from seeping in, the water-absorbing layer efficiently absorbing and storing water, and the protective layer providing physical protection and additional functions.

[0031] In another exemplary embodiment, the water-absorbing layer 200 includes ceramsite 220 and porous ceramics 210 , and the pores between the ceramsite 220 and the porous ceramics 210 are mixed and filled with cement mortar and highly absorbent resin.

[0032] In this embodiment, cement mortar or super absorbent resin can be filled separately in the pores between the ceramsite 220 and the porous ceramic 210, wherein, whether it is cement mortar or super absorbent resin, the ceramsite 220 and the porous ceramic 210 can be firmly bonded together to form an integral structure. This not only improves the mechanical properties of the composite material such as compression resistance and shear resistance, but also enhances its durability. In addition, the cement mortar itself has a certain water absorption, which can absorb part of the water in the early stage, alleviate the problem of rapid saturation of the surface, and as the water gradually penetrates into deeper layers, the cement mortar can provide additional storage space, thereby extending the water storage time. The super absorbent resin is a material specially designed to efficiently absorb and lock a large amount of water, and its water absorption can reach hundreds of times its own weight. When the ambient humidity decreases, the super absorbent resin can also slowly release the stored water to keep the ground moist, which is beneficial to air conditioning in the mine. However, after testing, it was found that the mixed filling of cement mortar and super absorbent resin was more effective than filling one of the materials alone. Cement mortar itself has a certain water absorption capacity. It can quickly absorb some water in the early stage to prevent the surface from being saturated too quickly, which helps to alleviate the problem of a large amount of water influx in a short period of time. Super absorbent resin is good at efficiently absorbing and locking a large amount of water, and its water absorption can reach hundreds of times its own weight. As the water gradually penetrates into deeper layers, super absorbent resin begins to play a role, providing additional storage space, and can slowly release water when the ambient humidity decreases to keep the ground moist, which is beneficial to air conditioning in the mine. When the two are mixed and filled, cement mortar serves as the initial water absorption medium, while super absorbent resin is responsible for deep storage and slow release of water, thus forming a graded water absorption-storage system, thereby improving the water treatment efficiency of the entire composite material. In addition, the mixed filling method can also combine the advantages of the two materials, so that the composite material has both the solid support provided by cement mortar and the elasticity and adaptability to moisture changes brought by super absorbent resin. This combination can effectively reduce stress concentration problems caused by changes in temperature and humidity, avoid the risk of cracking or failure that may occur in a single material, and thus enhance the long-term stability and durability of the composite material.

[0033] In addition, it should be noted that in the present application, the size of the ceramsite 220 and the porous ceramic 210 are both 10 mm. It has been verified that the size of 10 mm can ensure that the water-absorbing layer 200 has enough surface area for absorbing water, and the porosity will not be reduced due to the small particles, thereby affecting the water absorption speed. In addition, the 10 mm ceramsite 220 and porous ceramic 210 show good compressive strength when subjected to external pressure, and are not easy to break or deform, thereby improving the durability and service life of the entire composite material. If the size is too small (less than 10 mm), the material content per unit volume will increase, causing the water-absorbing layer to become more dense, thereby limiting the penetration and storage capacity of water. If the size is too large (greater than 10 mm), the total surface area per unit volume will be reduced, thereby reducing the chance of contact with water, thereby weakening the water absorption capacity of the water-absorbing layer.

[0034] In another exemplary embodiment, the ceramsite 220 and the porous ceramic 210 are arranged in a set shape.

[0035] In this embodiment, the ceramsite 220 and the porous ceramic 210 can be arranged in a tic-tac-toe pattern (eg Figure 2 By arranging the ceramsite 220 and the porous ceramic 210 in a crisscross pattern, a crisscross support structure can be formed, thereby enhancing the mechanical strength of the entire composite material, especially the compressive strength and shear strength. In addition, the ceramsite 220 and the porous ceramic 210 can also be arranged in a cross shape (such as Figure 3 As shown in the figure, compared with the tic-tac-toe arrangement, the criss-cross arrangement can provide more intersection points, thereby further enhancing the structural stability and overall rigidity of the entire composite material, thereby reducing the possibility of deformation.

[0036] However, whether it is a tic-tac-toe or a criss-cross pattern, both of these arrangements can make the gaps between the ceramsite 220 and the porous ceramic 210 more evenly distributed, thereby increasing the contact area with water, and then increasing the water absorption rate and capacity, ensuring that the water can be more effectively absorbed and stored, and avoiding rapid surface saturation. In addition, the tic-tac-toe and criss-cross grid structures can make the externally applied pressure more evenly distributed in all directions, preventing local overload from causing damage. Compared with a single-direction arrangement, the above two arrangements can better disperse stress and reduce the risk of cracks due to uneven loads.

[0037] Furthermore, this embodiment also provides another arrangement, that is, the ceramsite 220 and the porous ceramic 210 are arranged as follows: Figure 4The wavy shape shown. Compared with the tic-tac-toe and criss-cross arrangements, the wavy arrangement can provide a continuous support structure, which helps to better disperse the externally applied pressure. Compared with the tic-tac-toe and criss-cross arrangements, the wavy shape can distribute stress more evenly in multiple directions, thereby reducing local stress concentration and reducing the risk of cracks in the composite material due to uneven loads. In addition, the wavy arrangement can guide water flow along a specific path instead of directly penetrating the ceramsite 220 and the porous ceramic 210, which helps to control the distribution of water inside the composite material, ensuring that water can be stored more effectively, while slowing down the rate at which water penetrates into the bottom layer 100.

[0038] It should be noted that the above arrangement is described only as an example. In the composite material described in the present application, the ceramsite 220 and the porous ceramic 210 are not limited to the above arrangement. For example, a honeycomb arrangement (i.e., ceramsite 220 and porous ceramic 210 are arranged as a hexagonal grid structure), a mesh arrangement (i.e., ceramsite 220 and porous ceramic 210 are arranged as a continuous or discontinuous mesh pattern, such as a rhombus or square) or a trapezoidal stacking arrangement (i.e., ceramsite 220 and porous ceramic 210 are stacked at an angle to form a stepped structure), which will not be listed here. In short, any arrangement of the ceramsite 220 and the porous ceramic 210 that helps to absorb and store moisture is within the scope of protection of the present application.

[0039] In another exemplary embodiment, the components of the cement mortar and the mass percentage of each component are: 1% to 10% mineral powder, 1% to 5% nano-silica fume, 10% to 15% cement, 10% to 30% fast-hardening sulphoaluminate cement, 10% to 25% 40 to 70 mesh river sand, and 10% to 25% 70 to 140 mesh river sand.

[0040] In this embodiment, after experimental verification, the optimal mass percentage of the components of the cement mortar is: 10% mineral powder, 4% nano-scale silica fume, 15% cement, 30% fast-hardening sulphoaluminate cement, 25% 40-70 mesh river sand, and 16% 70-140 mesh river sand. At this ratio, the cement mortar has the best compressive strength, flexural strength, impermeability and wear resistance. In the cement mortar, the present application creatively introduces nano-scale silica fume, and the nano-scale particles can more effectively fill the tiny pores in the cement paste, thereby significantly improving the density of the mortar. In addition, due to its extremely fine particle size, it can greatly improve the impermeability of the mortar, thereby reducing the risk of water penetration. Further, the present application uses a combination of river sands of different particle sizes, wherein large-grained river sand (40-70 mesh) can provide skeleton support, help reduce the overall shrinkage rate of the mortar, and thus reduce the splitting caused by shrinkage; while small-grained river sand (70-140 mesh) can effectively fill the gaps between large particles, making the mortar more compact and smooth. By rationally combining two types of river sand with different particle sizes, the physical properties of the mortar can be optimized, ensuring that it exhibits good strength, durability and construction convenience in practical applications.

[0041] It should be noted that the mineral powder is preferably S95 mineral powder (S95 mineral powder has high volcanic ash activity and can react secondary with cement hydration products to generate more calcium sulfonate and calcium silicate hydrate (CSH), thereby improving the strength and durability of the mortar), the cement is preferably PO42.5 cement (PO42.5 cement is a general-purpose silicate cement. Compared with other types of ordinary cement, PO42.5 cement can show better strength growth rate in the early stage, which is conducive to shortening the construction period), and the fast-hardening sulphoaluminate cement is preferably 42.5 grade fast-hardening sulphoaluminate cement (42.5 grade fast-hardening sulphoaluminate cement can form a high-strength foundation in a relatively short time, and 42.5 grade fast-hardening sulphoaluminate cement can maintain a good hardening effect in low temperature or humid environment, and is very suitable for special environments, such as humid environments such as coal mines). In addition, the mesh river sand can be replaced by machine-made sand or quartz sand.

[0042] In another exemplary embodiment, the components of the super absorbent resin and the mass percentage of each component are: rice husk ash 7% to 20%, acrylic acid 16% to 35%, sodium hydroxide solution 7% to 30%, acrylamide 4% to 22%, benzoyl peroxide 0.3% to 0.6%, borax 0.01% to 1%, and flame retardant 0.1% to 0.4%.

[0043] In this embodiment, it is verified by experiments that the optimal mass percentage of the components of the super absorbent resin is: 17% rice husk ash, 33% acrylic acid, 29% sodium hydroxide solution, 20% acrylamide, 0.3% benzoyl peroxide, 0.4% borax, and 0.3% flame retardant. Under this ratio, the super absorbent resin can show the best water absorption capacity, so that it can quickly absorb a large amount of water in a short time and maintain it for a long time.

[0044] It should be noted that, compared with conventional water-absorbing resins, the water-absorbing resin used in this application introduces rice husk ash as a filler. The silicon dioxide component in rice husk ash can significantly improve the mechanical strength and thermal stability of the resin, and its porous structure helps to improve the water absorption performance. In addition, this application also introduces borax as a cross-linking agent. By introducing borax, additional cross-linking points can be formed to enhance the three-dimensional spatial structure of the resin, thereby improving the expansion stability and reusability of the resin after absorbing water.

[0045] In another exemplary embodiment, the protective layer 300 is made of polyester fiber material.

[0046] In this embodiment, the polyester fiber material is preferably waterproof and oil-proof polyester fiber, which can effectively resist the penetration of water and oil substances. The reason why the protective layer 300 is prepared by using polyester fiber material is that: first, polyester fiber has high strength and elastic modulus, which can provide effective physical protection to prevent external objects from damaging the water-absorbing layer 200 and the bottom layer 100; second, polyester fiber generally exhibits good acid and alkali resistance and solvent resistance, which enables it to maintain stable performance in complex environments; third, polyester fiber material has good wear resistance and can withstand frequent trampling of people or rolling of mechanical equipment.

[0047] In another exemplary embodiment, Figure 5 As shown, the protective layer 300 is provided with anti-skid protruding particles 310 , and the anti-skid protruding particles 310 are arranged at fixed intervals on the protective layer 300 .

[0048] In this embodiment, the anti-skid protrusion particles 310 are made of corundum wear-resistant materials (such as silicon carbide and silicon dioxide). Corundum has extremely high hardness and excellent wear resistance. For example, in the underground environment of a coal mine, the ground may be subject to frequent mechanical wear, heavy rolling, and erosion by chemical substances. Using corundum as the material of the anti-skid protrusion particles 310 can ensure that the anti-skid protrusion particles 310 can maintain their shape and function for a long time, providing continuous and effective anti-skid protection.

[0049] In addition, the anti-skid protrusion particles 310 are wrapped with high-density fabric (for example, polyester fiber, nylon, polypropylene and Teflon coated fabric). The high-density fabric can provide a more stable substrate, so that the anti-skid protrusion particles 310 can be more firmly adhered to the protective layer 300, so that even when subjected to external forces (such as trampling, friction or mechanical pressure), the risk of particle shedding can be reduced. If hard materials such as exposed corundum are directly used as anti-skid particles, material migration may occur during long-term use, that is, the anti-skid protrusion particles 310 are gradually ground or moved out of the original position. The wrapping of high-density fabric can effectively limit this migration and ensure that the position of each anti-skid point is fixed. Further, the high-density fabric can also be used as a barrier to prevent moisture and other harmful substances from directly contacting the inside of the anti-skid protrusion particles 310, thereby improving the durability and reliability of the entire waterproof composite material system.

[0050] Further, the present application designs the size and spacing of the anti-skid protrusion particles 310, wherein the height of the anti-skid protrusion particles 310 is set between 1mm and 5mm. If it is too high, it will cause inconvenience in walking or increase the wear of the sole; if it is too low, it will not provide sufficient friction to prevent slipping. The diameter of the anti-skid protrusion particles 310 is set between 3mm and 8mm. The particles within this diameter range can provide more obvious tactile feedback, which helps to improve the anti-skid performance, but if the particles are too large, the surface will be too rough, thereby affecting the comfort. The spacing of the anti-skid protrusion particles 310 is maintained between 5mm and 15mm. After inspection, the spacing within this range can ensure that the sole of the foot is in contact with multiple particles, thereby dispersing pressure and enhancing stability. In addition, the shape of the anti-skid protrusion particles 310 can be designed to be dome-shaped or conical, both of which can provide good grip without causing damage to shoes or skin.

[0051] Furthermore, on the basis of providing the anti-skid protrusion particles 310, the present application also provides luminescent particles 320 on the protective layer 300, and the luminescent particles 320 are made of self-luminous materials, such as zinc sulfide (ZnS)-based self-luminous materials, alkaline earth aluminate (AEAlO4)-based self-luminous materials, tritium lamps, etc. The luminescent particles 320 are evenly distributed between the anti-skid protrusion particles 310, and the luminescent particles 320 can continuously emit visible light in the absence of an external light source after absorbing a certain amount of energy (such as light, heat, electricity, etc.), thereby providing sufficient brightness guidance in a dark environment.

[0052] In another exemplary embodiment, the bottom layer 100 is made of ultra-light polyethylene material.

[0053] In this embodiment, the ultra-light polyethylene material refers to a polyethylene material with very low density characteristics after special process treatment, such as ultra-high molecular weight polyethylene, microporous polyethylene, cross-linked polyethylene, and linear low-density polyethylene. Polyethylene itself has good moisture resistance, and after optimization, the ultra-light polyethylene has more outstanding anti-seepage performance, which can effectively prevent moisture from penetrating below the bottom layer 100, thereby ensuring the dryness and safety of the ground. In addition, the ultra-light polyethylene material has a strong resistance to external environmental factors (such as ultraviolet rays, humidity changes, etc.), and is particularly suitable for complex and changeable working environments such as coal mines.

[0054] In another exemplary embodiment, Figure 6 As shown, the present application also provides a method for preparing a waterproof composite material, the method comprising:

[0055] S100: pre-treating the bottom layer 100, the water absorbing layer 200 and the protective layer 300;

[0056] In this step, the pretreatment of the bottom layer 100 includes: using plasma treatment equipment to perform surface activation treatment on the ultra-light polyethylene material to increase its surface energy and the number of active sites, and enhance the bonding force between subsequent adhesive layers. By increasing the surface energy of the bottom layer 100 material, it is ensured that a stronger and more durable interface is formed between it and the water-absorbing layer 200.

[0057] Pretreatment of the water-absorbing layer 200 includes: using a spraying or dipping method to uniformly coat a layer of hydrophilic nano-silicon dioxide (SiO2) on the surface of the expanded clay 220 and the porous ceramic 210 to increase the water absorption rate of the expanded clay 220 and the porous ceramic 210, while enhancing the bonding strength between the particles to prevent falling off during use.

[0058] The pretreatment of the protective layer 300 includes: embedding microcapsules containing healing agents in the polyester fiber material. These microcapsules can rupture and release the healing agents when the protective layer 300 is slightly damaged, automatically filling the cracks and restoring the protective function.

[0059] S200: placing the pretreated bottom layer 100 in a controlled environment (for example, the indoor temperature is stably controlled at 25±2°C, the relative humidity is maintained at 50±5%, the air is filtered through HEPA to ensure compliance with ISO Class 8 standards, the airflow in the room is strictly controlled, and the average wind speed does not exceed 0.2 m / s), then applying an adhesive to the surface of the pretreated bottom layer 100, heating to partially cure the adhesive, placing the pretreated water-absorbing layer 200 on the partially cured adhesive, and heating again to fully cure the adhesive, thereby completing the tight bonding between the pretreated bottom layer 100 and the water-absorbing layer 200;

[0060] S300: Applying adhesive to the surface of the water-absorbing layer 200 after bonding with the base layer 100, heating to partially cure the adhesive, laying the pre-treated protective layer 300 on the partially cured adhesive, and heating again to achieve complete curing of the adhesive, so that the pre-treated protective layer 300 and the water-absorbing layer 200 are bonded, and a waterproof composite material is formed after bonding.

[0061] In the above embodiments, the present application adopts a layered and gradual curing method to prepare a waterproof composite material. By adopting layered and gradual curing, it can be ensured that the adhesive in each step can be fully cured under the optimal conditions, avoiding the problem of incomplete curing in certain areas due to one-time curing. In addition, by controlling the curing conditions layer by layer, the generation of defects such as bubbles and voids can be effectively reduced, ensuring that the layers are tightly bonded, and improving the density of the overall structure. Furthermore, layered and gradual curing allows each layer to form a tighter molecular-level fusion with the next layer during the curing process, rather than simple surface bonding, thereby greatly enhancing the bonding force between the layers and improving the overall mechanical strength of the material.

[0062] In order to verify the superiority of the waterproof composite material described in the present application over some existing waterproof materials, the applicant conducted relevant tests on the waterproof composite material described in the present application and several existing waterproof materials (in order to avoid sensitivity, the present application replaces the specific waterproof material names with waterproof material A, waterproof material B, and waterproof material C). The test results are shown in Table 1:

[0063] Table 1

[0064]

[0065] As can be seen from Table 1, the waterproof composite material described in this application is significantly superior to several existing waterproof materials in multiple key performance indicators. Specifically, the composite material exhibits an extremely high water absorption rate (300%), which can quickly absorb and store a large amount of water, far exceeding existing materials; at the same time, it has excellent mechanical strength, with a compressive strength of 45MPa and a flexural strength of 8.5MPa, ensuring its stability and safety in complex environments. In addition, it also exhibits excellent chemical corrosion resistance, low wear (0.15g) and a high friction coefficient (0.85), which improves wear resistance and anti-slip properties, and is particularly suitable for harsh working conditions such as underground coal mines. The service life is expected to exceed 10 years, showing excellent durability and reducing long-term maintenance costs. The construction convenience score is as high as 9 points, which simplifies the installation process, and the 90% recyclability reflects its environmental protection and sustainability advantages. In summary, the waterproof composite material of this application is not only fully leading in performance, but also provides higher safety and economy in practical applications, showing obvious superiority.

[0066] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A waterproof composite material, characterized in that: The waterproof composite material comprises: A bottom layer (100), a water absorbing layer (200) and a protective layer (300) are sequentially stacked and attached, wherein: The water absorbing layer (200) is used to absorb and store external moisture; The bottom layer (100) is used to block the moisture stored in the water absorbing layer (200); The protective layer (300) is used to provide physical protection for the water absorbing layer (200) and the bottom layer (100).

2. A waterproof composite material according to claim 1, characterized in that: The water absorbing layer (200) comprises: Ceramsite (220) and porous ceramic (210), wherein the pores between the ceramsite (220) and the porous ceramic (210) are mixed and filled with cement mortar and highly absorbent resin.

3. A waterproof composite material according to claim 2, characterized in that: The ceramsite (220) and the porous ceramic (210) are arranged in a set shape.

4. The waterproof composite material according to claim 2, characterized in that: The components of the cement mortar and the mass percentage of each component are: Mineral powder 1%~10% Nano-silica fume 1%~5% Cement 10%~15% Rapid hardening sulphoaluminate cement 10%~30% 40~70 mesh river sand 10%~25% 70~40 mesh river sand 10%~25%.

5. The waterproof composite material according to claim 2, characterized in that: The components of the highly water-absorbent resin and the mass percentage of each component are: Rice husk ash 7%~20% Acrylic acid 16%~35% Sodium hydroxide solution 7%~30% Acrylamide 4%~22% Benzoyl peroxide 0.3-0.6% Borax 0.01%~1% Flame retardant 0.1%~0.4%.

6. The waterproof composite material according to claim 1, characterized in that: The protective layer (300) is made of polyester fiber material.

7. The waterproof composite material according to claim 1, characterized in that: The protective layer (300) is provided with anti-skid protruding particles (310), and the anti-skid protruding particles (310) are arranged in order at fixed intervals on the protective layer 300.

8. The waterproof composite material according to claim 1, characterized in that: Luminescent particles (320) are also provided on the protective layer (300), and the luminescent particles (320) are evenly distributed between the anti-slip protrusion particles (310).

9. The waterproof composite material according to claim 1, characterized in that: The bottom layer (100) is made of ultra-light polyethylene material.

10. A method for preparing a waterproof composite material, characterized in that: The method comprises: Pre-treating the bottom layer (100), the water absorbing layer (200) and the protective layer (300); Applying an adhesive to the surface of the pretreated bottom layer (100), heating to partially cure the adhesive, placing the pretreated water-absorbing layer (200) on the partially cured adhesive, and heating again to completely cure the adhesive, so that the pretreated bottom layer (100) and the water-absorbing layer (200) are bonded; The adhesive is applied to the surface of the water-absorbing layer (200) after bonding with the bottom layer (100), and the adhesive is partially cured by heating. The pre-treated protective layer (300) is laid on the partially cured adhesive, and the adhesive is heated again to completely cure, so that the pre-treated protective layer (300) and the water-absorbing layer (200) are bonded to form a waterproof composite material.